The Mediator subunit OsMED23 associates with the histone demethylase OsJMJ703 and the transcription factor OsWOX3A to control grain size and yield in rice - Luojiang Huang; Na Fang; Limin Zhang; Ran Xu; Baolan Zhang; Penggen Duan; Guansong Li; Yuehua Luo; Yunhai Li (Proceedings of the National Academy of Sciences, 2025)
Seed size is one of the important yield traits, and size control is also a fundamental developmental question. The knowledge about the genetic and molecular mechanisms that govern seed size is crucial for improving crop yield. Here, we report that the Mediator subunit OsMED23 associates with the histone demethylase OsJMJ703 and the transcription factor OsWOX3A to control grain size and weight in rice. Loss of function of OsMED23 or OsJMJ703 causes narrow and light grains, while overexpression of OsMED23 or OsJMJ703 results in large and heavy grains. OsMED23 physically interacts with OsJMJ703 and the transcription factor OsWOX3A. OsMED23, OsJMJ703, and OsWOX3A associate with the common promoter regions of two key grain size genes GW2 and OsLAC and repress their transcription by influencing H3K4me3 levels. Field trials demonstrate that overexpression of OsMED23 or OsJMJ703 can significantly increase grain yield. Therefore, our findings identify a mechanism by which the transcriptional repressor complex OsJMJ703-OsMED23-OsWOX3A determines grain size and weight by regulating gene expression and influencing H3K4me3 levels in rice, suggesting that this pathway has a great potential for improving grain yield in key crops.